How does Social Media Use Affect College Students’ Psychological, Subjective, and Social Well-being: The Mediating Role of Self-esteem - Chen, Huiyuan (Transactions on Economics, Business and Management Research, 2024)
This research examines the impact of social media use on the psychological, subjective, and social well-being of college students, with a focus on the mediating role of self-esteem. Social media has become an integral part of college students’ lives, offering platforms for information sharing, communication, and social interaction. However, the effects of social media on students’ well-being remain controversial. Some studies suggest that social media enhances social support, relationships, and belongingness, leading to improved mental health and subjective well-being. Conversely, other research highlights negative emotions, social anxiety, and feelings of loneliness resulting from social media use. Moreover, excessive attention to others’ social performances on social media may negatively impact college students’ self-esteem. This study aims to explore the relationship between social media use and the three dimensions of well-being while investigating the mediating role of self-esteem. By understanding the mechanisms underlying social media’s influence on students’ well-being, this research can provide insights for promoting healthier social media use among college students and improving their mental health and happiness.